Investigation of the systematic axial measurement error caused by the space variance effect in digital holography - Hao, Yan (2021)
Digital holography (DH) is one of the most promising quantitative phase measurement techniques and has been successfully used in 3D imaging and measurement. One of its attractive advantages is its excellent theoretical axial measurement accuracy of better than 1 nanometer. However, in practice, the axial accuracy has been quoted to be in the range of tens nanometers limited by the axial errors existing in DH system. In order to improve the axial measurement accuracy to approach the theoretical value, it is necessary to identify error sources and then reduce the errors according to their properties. In this paper, the space-variance effect of digital holography system is investigated and demonstrated to be an important systematic axial measurement error (SAME) source, especially for features with high frequency. The properties of the space-variant SAME are investigated through simulations and experiments. The object position, object height, object frequency content and object-CCD distance are found to be related to the space-variant SAME. Careful and appropriate placement of the object according to its features is thus necessary to reduce such SAME in a DH system. Based on the investigation, the guideline to appropriately position an object according to its properties is provided in this work.